PELUANG DAN KENDALA PENGEMBANGAN ITIK SERATI SEBAGAI PENGHASIL DAGING - Suryana Suryana (Jurnal Penelitian dan Pengembangan Pertanian, 2008)
Probability and constraint of mule duck development for meat production The demand for meat in South Kalimantan increases in line with the increasing of population, income, and people awareness on the role of animal protein for health. Meat supply is mainly originated from cattle and poultry. The alternative source of meat is mule duck, that is a crossing between muscovy and common duck. Mule duck has a potential to produce high quality meat and could be adapted with environment, resistant to disease, and could utilize low quality feed to become high quality meat. Mule duck farming in South Kalimantan is still conducted traditionally. This paper reviewed probability and constraint of mule duck development as meat source. The main constraints in mule duck development are supply of day old duck ( DOD ) , formulated feed supply, and postharvest handling. The increasing supply of DOD could be conducted by using artificial insemination and feed quality improvement with utilizating local feedstuffs by considerating nutrient value balances. Mule duck development should considerate farming location, the model of agribusiness development, marketing, farm scale, and continuity of feed supply.Keywords: Mule duck, productivity, meat production